Decreased MicroRNA-26a expression causes cisplatin resistance in human non-small cell lung cancer. Issue 5 (3rd May 2016) - Yang, Yong; Zhang, Peng; Zhao, Yanfeng; Yang, Jie; Jiang, Gening; Fan, Jie
ABSTRACT: Background: Lung cancer is the most common cancer that is caused by perturbation of regulatory pathways rather than dysfunction of a single gene. Cisplatin (CDDP; cis-diamminedichloroplatinum II) is the first member of a class of platinum-containing anti-cancer medication, which binds to DNA and triggers apoptosis. CDDP-based chemotherapy is used to treat various types of cancers. However, the efficacy of CDDP in the treatment of non-small-cell lung cancer (NSCLC) is limited by acquired drug resistance. MicroRNAs have recently emerged as key regulators of cancers, and miR-26a is one of down-regulated miRNAs in A549/CDDPres cell line. This study aimed to investigate the role of miR-26a in CDDP resistance in NSCLC as well as the underlying mechanisms. Methods: In this study, we analyzed expressional profiles of CDDP resistance-related mRNA, miRNA, and transcription factors (TF) that regulate miRNA expression in NSCLC. A549 cells were treated with CDDP, miR-26a mimic, or miR-26a inhibitor, and followed by biological analysis including drug sensitivity assay, colony formation assay, terminal-deoxynucleoitidyl Transferase Mediated Nick End Labeling (TUNEL) assay, and cell cycle analysis. Luciferase assay was used to determine the target of miR-26a. The regulation of miR-26a in Akt pathway was measured by western blot. Results: High mobility group A (HMGA) 2 was identified as the target of miR-26a. Overexpression of miR-26a in A549 cells inhibited G1-S transition, increased cell death in response to CDDP treatment, and decreased the colony formation of A549 cells. MiR-26a significantly decreased the expression of E2F1, diminished Akt phosphorylation, and downregulated Bcl2 expression. Cell growth was suppressed by inhibiting HMGA2-mediated E2F1-Akt pathway. Conclusion: MiR-26a is responsible for A549 cell sensitivity in the treatment of CDDP through regulating HMGA2-mediated E2F1-Akt pathway.